Dominant personalities in board committees, company characteristics, and internet environmental disclosure by Malaysian listed companies - Alarussi, Ali Saleh; Selamat, Mohamad Hisyam (Universiti Utara Malaysia, 2009)
This paper investigates the determinants of internet environmental disclosure (IED) amongst Malaysian listed companies. Ten variables have been tested using data collected from 170 Malaysian listed company websites, namely, dominant personalities in the audit committee, chairman of audit and nomination committees, dominant personalities in the audit and nomination committees, internationality, leverage, foreign shareholders, level of technology, firm age, number of shareholders, and listing status. It was found that internationality, foreign shareholders, level of technology, firm age, number of shareholders, and listing status are significantly affected by the level of IED. However, dominant personalities in the audit committee, chairman of audit and nomination committees, dominant personalities in the audit and nomination committees, and leverage did not show a significant relationship with the level of IED in Malaysia. The study provided some evidence to support signaling theory, shareholder accountability theory, and cost and benefit hypothesis in relation to internet disclosure.